농산촌의 어메니티 창출 전략과 과제 - 성주인 (한국농촌경제연구원, 2007)
Recently, there have been growing interests in rural amenities which are considered to be one of the most important parts of local assets. This study aims to explore the concept of rural amenities and suggest strategies and policy directions for developing and utilizing amenity resources in rural areas. The survey conducted in this study indicates that many people living in rural regions place high importance on amenity-oriented local development and have intention of participating in community activities which develop natural, traditional, and cultural resources in their locale. In order to have a more detailed knowledge of amenity-cultivating practices in countryside areas, two case studies were carried out in lakeside villages located in Hwacheon County and rural district of Baekun-Myeon in Jinan County. From these surveys we can get some indications regarding development of rural amenities: (1) institution building is important which promotes amenity-cultivation activities of residents and various stakeholders in rural communities, (2) working out a program connecting various resources in a community is the key to a successful amenity-led community development, (3) ordinary resources may contribute to enhancing the attractiveness of a place by cultural process discovering and valuing the uniqueness of local assets. In spite of the growing interest in rural amenities among residents and practitioners, there are only limited programs aimed at promoting activities of cultivating amenities of a rural community. Most local governments have no municipal planning system that can facilitate integrated development of various community resources. And it is not usual that residents and stakeholders in a locale actively participate in the process of developing rural amenities of their territory. To make livable rural communities, it is desirable that local governments and inhabitants take initiative in developing and creating rural amenities. And the central government needs to focus on sponsoring community-level activities which try to develop valuable local assets and utilize them in order to vitalize the territory. To support such activities, more flexible programs should be worked out and various kinds of policy tools need to be developed by the government. And a constant effort needs to be made nationwide to promote the value of rural amenities to the public and help people understand the need to implement policies of cultivating rural amenities. Finally, local partner groups are expected to play a more important role in amenity-led rural development processes. So municipal governments should build or strengthen partnerships for effective local governance system that may include various stakeholders, voluntary groups, and public bodies, etc. Researchers: Joo-In Seong and Mi-Ryung Song E-mail: jiseong@krei.re.kr